The Membrane Protein LasM Promotes the Culturability of Legionella pneumophila in Water - Li, Laam; Faucher, Sébastien P. (Frontiers in Cellular and Infection Microbiology, 2016)
The water-borne pathogen Legionella pneumophila (Lp) strongly expresses the lpg1659 gene in water. This gene encodes a hypothetical protein predicted to be a membrane protein using in silico analysis. While no conserved domains were identified in Lpg1659, similar proteins are found in many Legionella species and other aquatic bacteria. RT-qPCR showed that lpg1659 is positively regulated by the alternative sigma factor RpoS, which is essential for Lp to survive in water. These observations suggest an important role of this novel protein in the survival of Lp in water. Deletion of lpg1659 did not affect cell morphology, membrane integrity or tolerance to high temperature. Moreover, lpg1659 was dispensable for growth of Lp in rich medium, and during infection of the amoeba Acanthamoeba castellanii and of THP-1 human macrophages. However, deletion of lpg1659 resulted in an early loss of culturability in water, while over-expression of this gene promoted the culturability of Lp. Therefore, these results suggest that lpg1659 is required for Lp to maintain culturability, and possibly long-term survival, in water. Since the loss of culturability observed in the absence of Lpg1659 was complemented by the addition of trace metals into water, this membrane protein is likely a transporter for acquiring essential trace metal for maintaining culturability in water and potentially in other metal-deprived conditions. Given its role in the survival of Lp in water, Lpg1659 was named LasM for Legionella aquatic survival membrane protein.